INVESTIGATION AND IDENTIFICATION OF SOME ACTIVE BIOCHEMICAL IN MEDICAL PLANTS AGAINST CYP51 PROTEIN IN CANDIDA BY USING MOLECULAR DOCKING - Al Ghazal, Abubaker Abdulrahem Thanon; Khalil, Mohammad Ibrahim (Nativa (Sinop), 2023)
Common and medical plants were investigated for active biochemical to bind and inhibit the CYP51 protein in candida sp., 22 important plants were chosen and 263 molecular docking reactions were done between active materials and protein, 1441 different active ligands were detected for binding in protein active site, the best 225 ligands were chosen depending the power of affinity bond. Four ligands were candidates for having the best ligand affinity bond and more safety for use according to the toxicity test program; within these ligands, the Epicatechin was found to be the best biochemical for inhibition and bonding to CYP51 protein as it subjects to Lipinski's rule of five. Keywords: molecular docking; medical plants; Candida sp.